Reflections on leisure, play, and recreation - Jewell, David L. (Southern Illinois University Press, 1997)
"In this rich and unique reference, David L. Jewell compiles the first anthology of reflections on leisure, play, and recreation." "Disproportionately high budget cuts in parks and recreation services demonstrate too clearly society's view of leisure activities as frivolous and expendable. By selecting these voices of reason and making them available in a single volume, Jewell hopes to emphasize the "frailties of a capitalistic society's demeaning perception" of anything other than work. In this collection of wise words, he provides ammunition for those charged with selling leisure, play and recreation to the public and to political leaders." "Obviously, many of these quotations come from people actively engaged in the field of recreation, such as Charles K. Brightbill, widely published author and chair of the Department of Recreation and Municipal Park Administration at the University of Illinois. Political and social scientists also have stepped outside their major fields to contemplate and write about leisure. James C. Charlesworth, for example, was president of the American Academy of Political and Social Sciences when he wrote Leisure in America: Blessing or Curse? The clergy, too, has contributed to the debate, as have numerous psychologists and physicians. Joseph Lee, known as the Father of the Playground Movement, heads the list of lawyers represented here. Nor have philosophers been silent on this topic. Paul Weiss, for example, found it sufficiently engrossing to write the book Sport: A Philosophical Inquiry."--Jacket